Страстотерпицы: [сборник] / Валентина Сидоренко - Сидоренко Валентина Васильевна (Сибириада, 2020)
Экземпляры: ЦБ (20210303) / Инвентарный номер: 53231 / Цена: 305.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 34 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6